Analisis Pengaruh Pemahaman Sistem Modul Penerimaan Negara (Mpn) Terhadap Tingkat Kepatuhan Wajib Pajak Pada Kpp Metro (Study Kasus pada KPP Metro) - Herry Goenawan Sudarsa; Fitriya Kasmawati; Rosmiaty Tarmizi (Jurnal Akuntansi dan Keuangan, 2012)
The main objective of this study was to determine the perception and understanding of the corporate taxpayers Module System Revenue (MPN) and to know how to influence State Revenue System module (MPN) on tax compliance in paying taxes. Based on the analysis results, shows that the System Module Revenues have a positive influence on tax compliance in paying taxes. The system responded positively by the taxpayer, that is with a good understanding of which is owned by the taxpayer to the MPN system and increasing taxpayer compliance in paying taxes, especially in terms of formal compliance. This may imply that the expectation that the significant tax revenue from this system is not impossible. Based on the analysis results, the researchers suggested that the MPN system can continue to be applied by the government to increase the taxpayers and increase tax revenues. However, the implementation of such a system must be balanced with the supervision and implementation of sanctions against assertion, that the implementation of sanctions still considered fair by the taxpayer who continues to do tax obligations dutifully and correctly. It is expected that the tax authorities to be more active in conducting counseling and guidance to the Taxpayer on the importance of understanding the regulatory and taxation system, especially to increase taxpayer confidence in the regulatory and taxation systems. In addition, the tax authorities have to do counseling and guidance to the Board in terms of taxpayers comply with tax laws, especially for material compliance. It is expected to cause embarrassment in self- corporate taxpayer itself when it does not comply with tax laws. And the government should realize good governance and clean as well as improve the quality of tax officials in order to create a professional fiscus, honest / no corruption, and responsible in carrying out its duties and mandate given.